EVOO Enhance the Expression of Endothelial Marker and Vascular Endothelial Growth Factor in Preeclampsia Placenta Rat Models - Afniari, Maharani; Agnestia Naning Dian, Lovita; Yulia, Silvani; Wibi, Riawan (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Preeclampsia is a pregnancy complication marked by hypertension and proteinuria after 20 weeks of gestation, often leading to maternal and fetal morbidity and mortality. The disorder arises from endothelial dysfunction, causing impaired vascularization, inflammation, and reduced placental perfusion. Objective: This study aimed to analyze the effect of Extra Virgin Olive Oil (EVOO) on endothelial markers CD31, CD34, and Vascular Endothelial Growth Factor (VEGF) expression in a preeclampsia rat model. Method: A post-test-only control group design was applied with five groups: negative control (normotensive pregnant rats), positive control (preeclamptic rats without EVOO), and three treatment groups receiving EVOO at doses of 0.5, 1, and 2 ml/day for 18 days. Immunohistochemical examination was used to assess the expression of CD31, CD34, and VEGF. Result and Discussion: EVOO significantly increased CD31, CD34, and VEGF expression (p<0.05) compared to the positive control, with the highest increase at a dose of 2 ml/day. The rise in angiogenic markers indicates endothelial recovery and improved placental vascularization. Conclusions: EVOO has potential as supportive therapy in preeclampsia by enhancing endothelial function and angiogenesis, leading to better placental blood flow